Grid-Scale Battery Systems for VAR Support in Con Edison Distribution Substations via Bi-Directional Smart Inverters - Mohamed K. Kamaludeen; Yusef Esa; Kirn Zafar; Elihu Nyemah; Ahmed Ali A. Mohamed; Tamer Ibrahim; Simon Odie (IEEE Access)
Battery Energy Storage Systems (BESSs) play a pivotal role in enhancing the grid’s reliability by integrating Distributed Energy Resources (DERs) and offering a range of services, notably including reactive power (VAR) support through the use of bidirectional smart inverters. According to the literature review carried out and presented in this paper, it is evident that reactive power control for DER applications and grid have been examined in various studies. However, there is still a need to perform a thorough and explicit investigation on the VAR support impact on battery lifetime– we attempt to fill this gap with this study. This work aims to explore the effects of reactive power compensation provided by BESS smart inverters on the system’s lifespan, and to identify strategies for mitigating any potential negative impacts. For this purpose, a simulation was conducted on a 7.5MW/30MWh BESS connected to the grid at a Con Edison substation. The analysis revealed the significance of filter design on the DC side in mitigating battery current flow, thereby influencing the State of Charge (SoC) and extending the battery’s life. Implementing adequately sized inductive filters on both AC and DC sides proved effective in controlling battery current fluctuations while keeping the total harmonic distortion (THD) within acceptable ranges. Various scenarios were examined to ascertain the optimal inductive filter size that balances the BESS’s real and reactive power outputs. Additionally, simulations incorporating real-world grid elements at the substation were performed, including an evaluation of the combined effects of BESS VAR support with substation capacitor banks and shunt reactors. The findings suggest that inductive filters sized at 1mH and 5mH for both AC and DC interfaces can facilitate VAR support with minimal detrimental effects on BESS longevity. Moreover, a load flow analysis, integrating the BESS with Con Edison’s existing substation infrastructure, demonstrated the potential for bus voltage regulation and improvement by adjusting the BESS inverter’s reactive power settings.